Conservation of root‐fractured primary teeth—report of a case. Issue 6 (16th October 2012) - Liu, Xin; Huang, Jing; Bai, Yudi; Wang, Xiaojing; Baker, Andrew; Chen, Faming; Wu, Li‐an
Abstract: A 3.5‐year‐old girl presented to our clinic experiencing pain in her maxillary central incisors following traumatic injury during a fall. Radiographic examination revealed both primary maxillary central incisors with mid‐root and apical third horizontal root fractures, respectively. Splinting with orthodontic brackets and stainless steel wire was performed. At 2 weeks, resorption of the apical fragments in both injured teeth was observed, and after 3 months, almost complete resorption was noted on radiographs. Tooth mobility at this point was back to physiologic levels and the splint was removed. After 2.5 years, the primary maxillary incisors were replaced by permanent incisors demonstrating normal tooth color, position, and root development. Although this case illustrated the favorable prognosis of two primary teeth with root fractures and severely mobile coronal fragments by a conservative approach, more scientific evidences are needed and frequent recalls are necessary when primary root fractures are attempted to be managed with splinting.